2002
DOI: 10.1614/0043-1745(2002)050[0530:dbcwaw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dry bean competitiveness with annual weeds as affected by soil nutrient availability

Abstract: Productivity of dry bean is constrained by the competition with weeds for scarce nutrients and water in eastern Africa. Trials were conducted at Cornell University in 1996 and in central Uganda during the two seasons of 1997 to test the hypothesis that bean crop nutrition can be improved while increasing the relative competitiveness of bean with annual weed species. Soil levels of available N, P, and K were varied in the main plots. Subplots consisted of bean and two weed species in pure stands and bean mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
2
18
0
1
Order By: Relevance
“…Everaarts (1992) reported that N and phosphorus (P), but not potassium (K), application stimulated weed growth on a sandy loam soil. Similarly, Ugen et al (2002) observed greater weed growth in a non-weeded bean (Phaseolus vulgaris) crop with N and P application. Fertiliser can also favour certain weeds and therefore has the potential to shift weed species (Liebman and Mohler 2001).…”
Section: Cropping System and Fertilizer Interaction On Weed Densitymentioning
confidence: 78%
“…Everaarts (1992) reported that N and phosphorus (P), but not potassium (K), application stimulated weed growth on a sandy loam soil. Similarly, Ugen et al (2002) observed greater weed growth in a non-weeded bean (Phaseolus vulgaris) crop with N and P application. Fertiliser can also favour certain weeds and therefore has the potential to shift weed species (Liebman and Mohler 2001).…”
Section: Cropping System and Fertilizer Interaction On Weed Densitymentioning
confidence: 78%
“…The results indicated that weed growth response to CPM was not explained by K or N added (with the exception of velvetleaf). In another study, Ugen et al (2002) evaluated dry bean's competitiveness against the following annual weeds: Solanum nigrum, Bidens pilosa and Galinsoga parviflora. The results revealed that the weed nutrient uptake and growth was increased with N and P application, whereas the relative competitiveness of bean was increased further to K application.…”
Section: Referencesmentioning
confidence: 99%
“…Em relação à avaliação realizada no final da formação de propágulos, o feijão foi a espécie que apresentou o maior teor de P em seus tecidos, apenas não diferindo do encontrado para os biótipos de E. hetrophylla na dose de P de 24,00 mg dm -3 e de D. tortuosum na dose de P de 48,00 mg dm -3 (Quadro 5). Todavia, Ugen et al (2002) observaram menor concentração de P na massa seca de plantas de feijão (3,2 a 3,8 mg g -1 ) em comparação à das plantas daninhas Bidens pilosa (3,7 a 4,1 mg g -1 ), Galinsoga parviflora (4,0 a 4,8 mg g -1 ) e Solanum nigrum (4,0 a 4,5 mg g -1 ). B. pilosa e soja foram as espécies que menos concentraram P em seus tecidos.…”
Section: Resultsunclassified